Multimodality approach to optical early detection and mapping of oral neoplasia - Ahn, Yeh-Chan; Chung, Jungrae; Wilder-Smith, Petra; Chen, Zhongping (Journal of biomedical optics, 2011)
Early detection of cancer remains the best way to ensure patient survival and quality of life. Squamous cell carcinoma is usually preceded by dysplasia presenting as white, red, or mixed red and white epithelial lesions on the oral mucosa (leukoplakia, erythroplakia). Dysplastic lesions in the form of erythroplakia can carry a risk for malignant conversion of 90%. A noninvasive diagnostic modality would enable monitoring of these lesions at regular intervals and detection of treatment needs at a very early, relatively harmless stage. The specific aim of this work was to test a multimodality approach [three-dimensional optical coherence tomography (OCT) and polarimetry] to noninvasive diagnosis of oral premalignancy and malignancy using the hamster cheek pouch model (nine hamsters). The results were compared to tissue histopathology. During carcinogenesis, epithelial down grow, eventual loss of basement membrane integrity, and subepithelial invasion were clearly visible with OCT. Polarimetry techniques identified a four to five times increased retardance in sites with squamous cell carcinoma, and two to three times greater retardance in dysplastic sites than in normal tissues. These techniques were particularly useful for mapping areas of field cancerization with multiple lesions, as well as lesion margins.